The economy of migrants from Puebla living in New York City - Corona Jiménez, Miguel Ángel (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2014)
In the last decade, the number of poblanos migrants in New York City has grown rapidly. The following research presents the results obtained from a survey about the economy of these migrants. This means information about their income and expenses. Furthermore, data about the amount, frequency and destination of the remittances sent to their hometown communities are also provided. The main social, demographic and labor characteristics that affect their economic behavior are analyzed. The composition of their income and expenses is studied. It is proved that the majority of them live in poor and precarious conditions so that they can send more money to their families. One of the main findings is that they spend most of their income in remittances and the rent of their shared apartments. In general, these migrants want to return to Mexico once they have the money to build a house or open a business. Finally, this research confirms that the main cause of migration is economical situation and the wage differential between Mexico and United States
Keywords: Mexican Migration. New York Migrants. Household